2013
DOI: 10.2166/wst.2013.643
|View full text |Cite
|
Sign up to set email alerts
|

Polyhydroxyalkanoate (PHA) production from sludge and municipal wastewater treatment

Abstract: Polyhydroxyalkanoates (PHAs) are biodegradable polyesters with comparable properties to some petroleum-based polyolefins. PHA production can be achieved in open, mixed microbial cultures and thereby coupled to wastewater and solid residual treatment. In this context, waste organic matter is utilised as a carbon source in activated sludge biological treatment for biopolymer synthesis. Within the EU project Routes, the feasibility of PHA production has been evaluated in processes for sludge treatment and volatil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(57 citation statements)
references
References 1 publication
2
55
0
Order By: Relevance
“…Following the outcomes of Coats et al (2007b) and Morgan-Sagastume et al (2014), where the authors showed the feasibility of selecting a biomass with PHA storage capacity under feast-famine with municipal wastewater, efforts were made to integrate wastewater treatment with the PHA production. At lab scale, Valentino et al (2015) conducted a MMC selection stage using a synthetic medium mimicking municipal wastewater similar to an activated sludge process.…”
Section: Molecular Fingerprintingmentioning
confidence: 99%
“…Following the outcomes of Coats et al (2007b) and Morgan-Sagastume et al (2014), where the authors showed the feasibility of selecting a biomass with PHA storage capacity under feast-famine with municipal wastewater, efforts were made to integrate wastewater treatment with the PHA production. At lab scale, Valentino et al (2015) conducted a MMC selection stage using a synthetic medium mimicking municipal wastewater similar to an activated sludge process.…”
Section: Molecular Fingerprintingmentioning
confidence: 99%
“…Nonetheless, when using real wastewater the experimental results indicated that PHA production is primarily associated with the VFA fraction of the wastewater (Coats et al, 2007;Bengtsson et al, 2008;Beccari et al, 2009;Albuquerque et al, 2010;Morgan-Sagastume et al, 2010;Jiang et al, 2012;Tamis et al, 2014a;Morgan-Sagastume et al, 2014, 2015Korkakaki et al, 2016). This correlation is based on the fact that the VFA carbon fraction serves as a PHA precursor and efficiently enriches for a PHA accumulating community.…”
Section: Introductionmentioning
confidence: 97%
“…Further concepts are already discussed for optimizing the energy management of primary wastewater treatment, e.g., using moving bed biofilm reactors or applying full anaerobic treatment of wastewater (McCarty et al, 2011;Jenicek et al, 2012;Ødegaard, 2016). Furthermore, microorganisms converting wastewater in valuable products (e.g., fatty acids and polyhydroxyalkanoates) and microbial electrochemical technologies (METs) constitute examples of further opportunities for wastewater treatment and valorization (Yamasaki et al, 2006;Logan, 2009;Rabaey and Rozendal, 2010;Morgan-Sagastume et al, 2014). Independent from the specific process for exploiting the chemical energy of wastewater, comprehensive information on its energy content is necessary to evaluate the economic viability of such processes.…”
Section: Introductionmentioning
confidence: 99%